PEMBELAAN ADVOKAT TERHADAP KLIEN DALAM MENANGANI PERKARA HUKUM MENURUT PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Huda, Miftahul (UIN Sunan Kalijaga Yogyakarta, 2012)
Advocate profession is a very noble profession, which setatusnya alignedwith other law enforcement agencies, such as police, prosecutors andjudges. Status as a law enforcement together with other law enforcementagencies contribute to the implementation of any fair trial, fair, andlegal certainty for all seekers of justice in enforcing the law, truth,justice and human rights. Advocate actually have a special role in theenforcement of judicially recognized. The role of special advocates areagainst the interests of the accused, the accused and those seeking justice,in accordance with the profession as those who provide legal services inand out of court. There are some that must be considered by an advocatebefore accepting the power of the client to resolve his case in court, areas follows: in the case of a civil or criminal problematic, there is apower law or not, and the evidence is authentic, and the witnesseswitnesses. Pleading for Handling Client Advocate tehadap lawsuitin Islam based on the Quran and as-Sunnah, while the positive law isregulated in Law Number 18 Year 2003 regarding the Code of EthicsAdvocate and Advocate Indonesia.